COLL 613-Studies on the vapor-phase photo-oxidation of methanol over nano-size titania clusters dispersed in MCM-41 mesoporous silica - Kumar, Dharmesh; Bhattacharyya, Kaustav; Tripathi, Arvind; Varma, Salil; Gupta, Narendra M. (Abstracts of Papers of the American Chemical Society, 2006)

Synergistic role of acid sites in the Ce-enhanced activity of mesoporous Ce-Al-MCM-41 catalysts in alkylation reactions: FTIR and TPD-ammonia studies - Kalita, Pranjal; Gupta, Narendra M.; Kumar, Rajiv (Journal of Catalysis, 2007)
The acidic properties of Ce-x-Al-y-MCM-41 with different Ce/Al/Si atomic ratios were examined by pyridine-FTIR and ammonia-TPD methods. Both the density and the strength of the acid sites were considerably higher in the samples containing both Ce and Al than in the samples with only one of these substituents. The IR spectra of chemisorbed pyridine revealed that the Ce-Al-MCM-41 samples contained at least two distinct Lewis acid sites, L-2 (1595-1444 cm(-1)) and L-1 (1613-1452 cm(-1)), where the L-2/L-1 ratio increased progressively with increasing Ce/Al atomic ratio in a series of samples with similar Si/Al ratios. In addition, the density of the Bronsted acid sites (B) as well as the B/L-1 ratio increased with increasing Ce/Al molar ratio in these samples. The findings of this study help us understand the synergistic role played by Lewis and Bronsted acid sites in the catalytic activity of these catalysts for the benzylation of toluene. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Structure sensitivity of nano-structured CdS/SBA-15 containing Au and PtCo-catalysts for the photocatalytic splitting of water - Lunawat, Puja S.; Kumar, Rajiv; Gupta, Narendra M. (Catalysis Letters, 2008)
Photocatalysts containing nanocrystallites of cadmium sulphide dispersed in the channels of mesoporous silicate SBA-15 exhibited enhanced activity for visible-light mediated splitting of water, as compared to bulk CdS. Whereas the incorporation of 1 wt.% Pt co-catalyst in CdS/SBA-15 led to a substantial increase in H-2 yield, Au at similar loading resulted in marginally decreased activity. The results indicate that the photocatalytic activity of CdS crystallites is structure sensitive. Similarly, the role of a noble metal may be associated with the particle size dependent micro-structural features, rather than its electronic properties such as the work function or the heat of adsorption of reactant or product molecules.
Keywords: nano-structured cadmium sulphide; Photocatalysis; role of noble metal co-catalyst; Splitting of water; structure sensitivity

Uranyl-anchored MCM-41 as a highly efficient photocatalyst in the oxidative destruction of short chain linear alkanes: an in situ FTIR study - Krishna, Vidya; Kamble, Valmik S.; Gupta, Narendra M.; Selvam, Parasuraman (Journal of Physical Chemistry C, 2008)
Uranyl ions anchored in the mesopores of MCM-41 molecular sieve were found to be a highly efficient heterogeneous photocatalyst in the complete degradation of short chain linear alkanes such as methane, ethane, propane, and butane, carried out under ambient conditions of light irradiation. In addition to the formation of carbon dioxide and water, a negligible amount of methane was detected during the photooxidation of ethane, propane, and butane. Further, small amounts of ethane were also obtained during photooxidation of butane, suggesting quenching of *UO22+ by a C-C bond cleavage, in addition to a hydrogen atom abstraction. An C, in situ Fourier transform IR spectroscopy analysis was employed in order to monitor the photooxidation of methane and ethane over *UO22+/MCM-41, where formic acid, formaldehyde, and formate species were the transient species identified from methane, and acetic acid, acetaldehyde, and acetate species were the intermediates obtained from ethane. Appropriate reaction pathways were proposed based on the formation of these species (C-H cleavage) and also from the negligible quantitites of methane and ethane obtained during photooxidation of higher alkanes (C-C cleavage).

Doping-induced microstructural, textural and optical properties of In2Ti1-xVxO5+delta semiconductors and their role in the photocatalytic splitting of water - Shah, Pallavi; Bhange, Deu S.; Deshpande, Aparna; Kulkarni, Mukund S.; Gupta, Narendra M. (Materials Chemistry and Physics, 2009)
The physicochemical properties of V-doped indium titanates (In2Ti1-xVxO5-delta, 0.0 <= x <= 0.2) were investigated by using XPS, powder XRD, UV-vis, SEM and luminescence spectroscopy techniques. The Rietveld refinement of XRD data revealed that even though the V-containing samples were isostructural with In2TiO5 (orthorhombic space group Pnma), a systematic x-dependent variation was noticeable in the Ti-O bond lengths in [TiO6] octahedral units, cell parameters and in the value of delta. XPS results confirmed the coexistence of V5+ and V4+ states, leading thereby to an enhancement in oxygen non-stoichiometry in the doped samples. A loading-dependent progressive shift from 400 to 750 nm was also observed in the onset of the absorption edge, indicating a significant narrowing of the band gap. Furthermore, the samples with higher V-content were comprised of the grain clusters having larger size and an irregular shape. The UV-vis. photoluminescence and thermoluminescence studies indicate that the doping-induced lattice defects may give rise to certain closely spaced acceptor/donor energy levels in between the band gap of host matrix. The indium titanates are found to serve as stable photocatalysts for water splitting under visible light, where oxygen was the major reaction product. The role of microstructural and morphological properties in the photocatalytic activity is discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In2Ti1-xVxO5+delta photocatalysts; Luminescence spectroscopy; Microstructure; Optical properties; Structure-activity relationship; water splitting

Interfacial and physico-chemical properties of polymer-supported CdS center dot ZnS nanocomposites and their role in the visible-light mediated photocatalytic splitting of water - Deshpande, Aparna; Shah, Pallavi; Gholap, Ramkrishna S.; Gupta, Narendra M. (Journal of Colloid and Interface Science, 2009)
Nano-composite CdS center dot ZnS moieties coated over polyester strip were found to exhibit better visible-light-mediated photo-activity for splitting of water, as compared to corresponding pure CdS or ZnS containing coupons. This increase in activity depended upon the mol ratio of the two component sulphides in a particular sample. HRTEM experiments revealed the presence of 1-3 nm size CdS particles embedded over larger size ZnS clusters, the composite samples thus functioning as a highly dispersed guest-host system. In the case of CdS and ZnS dispersed individually over polyester, average crystallite size was found to be around 5 and 15 rim, respectively. A blue shift was observed in the UV-vis absorption spectrum of US oil addition of ZnS, in conformation with the quantum size effects. Powder XRD, electron diffraction and XPS Studies showed that the nanocomposites were comprised of the face-centered cubic (alpha) phases of both US and ZnS in a close contact with each other. At the same time, certain solid solution phases, i.e. Cd(1-x)Zn(x)S. were generated at the interfaces of these two semiconductors. Our Study demonstrates that the increase in the number of reaction sites due to smaller size of US particles and the micro-structural properties associated with the nanostructured US or CdS/ZnS interfaces may together play a vital role in the augmented catalytic activity of CdS center dot ZnS composite photocatalysts. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: CdS center dot ZnS nanocomposites; Photocatalytic activity; Role of microstructural properties; Splitting of water

Physico-chemical, photo-catalytic and O-2-adsorption properties of TiO2 nanotubes coated with gold nanoparticles - Malwadkar, Sachin S.; Gholap, Ramkrishna S.; Awate, Shobhana V.; Korake, Prakash V.; Chaskar, Manohar G.; Gupta, Narendra M. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Gold-containing titania nanotubes (Au/NT) were found to display higher activity for photooxidation of acetaldehyde, as compared to corresponding gold-free nanotubes and also a Degussa P-25 catalyst. Besides CO2 as a major reaction product, small amounts of H-2, CH4, CO, H2O and CH3COOH were also formed, irrespective of the catalyst employed. High-resolution TEM examination showed that most of the gold particles in Au/NT were of 1.5-5 nm size, distributed both within and at outside surface of the nanotubes. Some larger size (10-70 run) clusters were also seen at the external surfaces, particularly in the samples calcined at an elevated temperature. The temperature-programmed desorption measurements revealed that, compared to P-25 TiO2, a significant entrapment of O-2 occurred at two distinct tubular sites of NT samples, corresponding activation energy of desorption (E,) being around 36 and 41 kcal mol(-1). On the other hand, gold nanoparticles in Au/NT served as independent low-energy (E-a = 26 kcal mol(-1)) sites for adsorption/activation of O-2. These adsorptive properties of TiO2 and Au were lost completely on calcination, thus revealing a crucial role played by the particle size. In situ IR spectroscopy results showed that room-temperature exposure to acetaldehyde + air gave rise to a molecularly bound state, i.e. CH3CHOad, over both NT and Au/NTsamples, which in turn transformed quickly to yield certain acetate (CH3COOad-) and formate (HCOOad-) type transient species with the involvement of the surface OH groups. The decomposition and oxidation of these surface species with the help of O-2(-), O-ad and hydroxyl ion radicals (OH-) formed at photo-excited Au/NT interfaces led to the reaction products mentioned above. We conclude that, besides electron-hole charge separation, the adsorptive properties of host matrix and nanosize gold may together play a significant role in deciding the photo-catalytic properties of Au/TiO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Acetaldehyde oxidation; Gold co-catalyst; O-2-adsorption; Photo-catalytic activity; TiO2 nanotubes

Critical role of particle size and interfacial properties in the visible light induced splitting of water over the nanocrystallites of supported cadmium sulphide - Deshpande, Aparna; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2010)
CdS crystallites of varying size (1 to 5.0 nm) were successfully deposited on the surfaces of polyester and activated charcoal. The size and the texture of these crystallites depended on CdS loading and also on the substrate morphology. These highly dispersed photocatalysts displayed a pyramidal trend in activity for visible light induced splitting of water molecules, similar to that reported for the heterogeneous catalytic reactions over supported noble metals. Thus, the CdS particles of similar to 2.5 nm size gave rise to maximum rate of H(2) evolution as compared to the particles of either smaller or of larger size. The particles of <1.5 nm diameter were of poor crystallinity and displayed a significant Q-size effect on the absorption edge. Our study provides direct evidence for the structure sensitivity of photocatalytic dissociation of water over supported semiconductor nanocrystallites, where the particle size and the interfacial microstructural defects played a vital role. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS nanocrystallites; Interfacial defects; Photocatalysis; Structural sensitivity; water splitting

Nature of the acid sites in the metal triflates immobilized in SBA-15 and their role in the friedel-crafts acylation of naphthalene - Selvakumar, S.; Gupta, Narendra M.; Singh, A. P. (Applied Catalysis A-General, 2010)
The Zn-triflate molecules loaded (5-30 mol%) in mesoporous SBA-15 silicate exhibited considerably higher catalytic activity for liquid-phase Friedel-Crafts (FC) acylation of naphthalene with p-toluoyl chloride, as compared to the corresponding triflates of La, Ce and Y. In situ FTIR studies revealed that the triflate molecules occluded in the channels of SBA-15 may cause severe perturbation of surface hydroxyl groups, without undergoing an electronic binding. The metal cations of the triflate molecules, on the other hand, participated in direct bonding of the reactant molecules and also helped in the formation of some Bronsted type surface acid sites. This article discusses the role of the acid sites generated on occlusion of metal triflates in SBA-15, as monitored by using NH(3)-TPD and pyridine-IR spectroscopy, in the Friedel-Crafts acylation of naphthalene. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acylation; Mesoporous silica; Metal triflate; Naphthalene

Photodegradation of methanol under UV-visible irradiation by titania dispersed on polyester cloth - Bhattacharyya, Kaustava; Tripathi, Arvind K.; Gupta, Narendra M.; Tyagi, Avesh K. (Photochemistry and Photobiology, 2010)
Titania supported on polyester fabric (TiO(2)-PY) with varying titania loadings (2-7 wt%) were prepared via the dip-coating method at room temperature using an aqueous slurry of anatase titania. Structural and morphological characterizations by X-ray diffraction and scanning electron microscopy revealed that the titanium dioxide crystallites deposited on the surface of the polyester fabric were in the micrometer range while their phase remained to be anatase. Photocatalytic activity of TiO(2)-PY fabric catalysts was evaluated for vapor-phase oxidation of methanol in air as a test reaction in the presence of UV as well as solar radiation under ambient conditions. These catalysts were found to be quite active in both UV and solar irradiation with activity being higher in the former case. CO(2) yield from photo-oxidation of methanol depended on titania content and also on its dispersion over polyester fabric support.

Solvent-free mukaiyama-aldol condensation catalyzed by Ce-Al-MCM-41 mesoporous materials - Kalita, Pranjal; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2011)
MCM-41 samples containing Ce4+ and Al3+ in the network, designated as Ce-x-Al-MCM-41 (x = 0.0-0.04), were synthesized and characterized systematically. These samples exhibited higher catalytic activity for Mukaiyama-aldol condensations to produce beta-hydroxy carbonyl compounds under the solvent free conditions, compared to the samples containing either of the two cations. The product yield was found to depend on the electron donating/withdrawing characteristics of reactant molecules being responsible for the observed trend. Series of solvents were also investigated but considerably high yield of aldol products (similar to 95%) could be achieved without using any solvents. In all the cases, the selectivity was found to be 100%, typical of such Mukaiyama-aldol condensations. The higher catalytic activity of Ce-x-Al-MCM-41 is explained on the basis of certain new acid sites generated due to co-incorporation of Ce and Al cations. Published by Elsevier Inc.
Keywords: Acid catalyst; Ce-Al-MCM-41; Silyl enol ether and aldehyde; Silyl ketene acetal

Visible-light-induced photosplitting of water over gamma `-Fe4N and gamma `-Fe4N/alpha-Fe2O3 nanocatalysts - Dhanasekaran, P.; Salunke, Hemant G.; Gupta, Narendra M. (Journal of Physical Chemistry C, 2012)
The application of gamma'-Fe4N, a noble-metal-free, low-cost catalyst, in the photosplitting of neat water into stoichiometric amounts of H-2 and O-2 under visible-light irradiation is reported for the first time. The catalyst showed optical absorption and photoluminescence emission bands in the entire visible region. The photocatalytic water-splitting activity was wavelength-dependent, the quantum efficiency for H-2 evolution being ca. 1.7 and 0.7% at excitation wavelengths of 450 and 500 nm, respectively. Addition of electron donor/acceptor sacrificial reagents considerably affected the yield and stoichiometry of H-2 and O-2. At the same time, the product yield increased in a composition-dependent manner for (gamma'-Fe4N)(x) + (alpha-Fe2O3)(1-x) nanocomposites. This activity augmentation is ascribed to the better dispersion of the active component gamma'-Fe4N and also to the availability of more active surface sites at Fe4N/Fe2O3 contacts. Moreover, the proximity of the valence band potential of the component photosystems promotes the preferential transfer/entrapment of photoexcited hole carriers. We envisage that the defect/impurity-induced interband-gap energy states may play a vital role in these charge-transfer processes, leading thereby to more effective e(-)-h(+) separation and the enhanced rate of the water-splitting reaction. First-principles electronic structure analysis suggests that the extraordinary photocatalytic and optical properties of intermetallic gamma'-Fe4N may arise from the particle-size-dependent changes in electronic structure.

Novel, band-controlled metal oxide compositions for semiconductor-mediated photocatalytic splitting of water to produce H-2 - Gupta, Narendra M. (57th DAE Solid State Physics Symposium, 2013)

Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Photophysical, bandstructural, and textural properties of o-FeNbO4 in relation to its cocatalyst-assisted photoactivity for water oxidation - Babu, Robin; Kelkar, Sarika A.; Kashid, Vikas; Achary, Srungarpu N.; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2014)
In this study, a relationship between physicochemical, photophysical and photocatalytic properties of hydrothermally synthesized orthorhombic iron niobate (FeNbO4) is investigated. o-FeNbO4 displayed a multi-regime optical absorbance, which was ascribed to at least two distinct phenomena: (i) bandgap (similar to 3.4 eV) excitation giving rise to UV absorbance and (ii) energy transitions involving disorder-induced sub-bandgap donor or acceptor states leading to visible light absorbance. The preparation-dependent distortion in the crystal lattice and the existence of closely spaced inter-bandgap energy states were corroborated by powder X-ray diffraction, photoluminescence, thermoluminescence, and Raman spectroscopy studies. The first principles electronic structure elucidation and photoelectrochemical measurements supported a wide bandgap for FeNbO4, in contrast to the narrow bandgap reported previously. Correspondingly, a small photocurrent density was observed for FeNbO4 (similar to 2 to 3 mu A cm(-2)) under 1 sun illumination, suggesting the availability of a smaller cross section of photogenerated charge pairs. Following these band characteristics, while no H-2 evolution was observed, FeNbO4 gave rise to particle size-dependent O-2 evolution during visible light irradiation of water in the presence of electron scavengers, the samples loaded with NiO as cocatalyst showing better activity. Further, the transmission electron microscopy examination revealed the dominant exposure of (011) facets of FeNbO4, besides a significant heterogeneity of inter-domain boundaries. Overall, our results confirm that the photoactivity of metal/oxide nanocomposites is governed by a combination of factors, such as: grain morphology, microstructure, surface adsorption states, and the localized inter-bandgap energy states. Our study also reveals that, in contrast to prevalent assumptions, the wavelength at the absorption edge may not represent the true band-to-band energy gap of metal oxide semiconductors, which is relevant to their photocatalytic activity.

Role of aliovalent cation doping in the activity of nanocrystalline CdS for visible-light-driven H-2 production from water - Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2015)
This study was aimed at discerning the enhancement in the visible-light-driven water splitting activity of nanocrystalline CdS photocatalysts because of their doping with a small amount of an aliovalent cation (Ag+ or Cr3+). The CdS/Cr-x (x = 0-2.3 wt%) and CdS/Ag-x (x = 0-1.5 wt%) samples, which were synthesized using a one-step hydrothermal method, were characterized systematically for their crystallographic, morphological, interfacial, and photo-physical properties. The Rietveld refinement of the powder X-ray diffraction data enabled us to quantify the doping-effect on the phase composition and lattice parameters. As compared to pure CdS, the samples containing similar to 0.2 wt% of Cr or Ag showed two or tenfold enhancement in the rate of H-2 evolution from water, respectively, when sulfide-sulfite ions were used as sacrificial electron donors. This pyramidal trend, i.e. maximum activity for a specific impurity content, which decreased on decreasing as well as increasing the amount of doping, did not occur owing to the presence of a secondary-phase metal sulfide or a dispersed metal cocatalyst. Our study revealed that instead of the widely advocated mechanism involving inter-semiconductor or semiconductor-to-metal electron transfer steps, the doping-modified photoactivity of CdS was governed by certain bulk and surface properties such as the cation-dependent particle nucleation, dominance of hex-CdS facets, and structural defects. Additionally, impurity-induced sub-bandgap charge-trapping states also contributed to the overall quantum efficiency. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.

Quenching effect of uranyl species in the photoluminescence emission and visible-light-driven water dissociation activity of CdS and TiO2 photocatalysts - Gupta, Narendra M.; Kelkar, Sarika A.; Korake, Prakash V. (Photochemical & Photobiological Sciences, 2016)
Anchoring of uranyl species (2-4 mol%) led to the complete quenching of photoluminescence emission and the visible-light-driven water photodissociation activity of TiO2 (Degussa-P25) and a hydrothermally synthesized CdS photocatalyst. Photophysical measurements revealed a fast relaxation and the transfer of photogenerated electrons/energy from the TiO2 or CdS substrate to the acceptor uranyl moieties. Besides the position of flat band levels, significant overlap of the absorption/emission spectra of the host matrix and the surface-bound UO22+ species is responsible for this reverse energy transfer from a wide bandgap semiconductor to a material with a smaller band-to-band energy gap.

Factors affecting the efficiency of a water splitting photocatalyst: a perspective - Gupta, Narendra M. (Renewable & Sustainable Energy Reviews, 2017)
To design an efficient photocatalyst (PC) for semiconductor (SC)-mediated, solar-driven water dissociation to generate hydrogen, a host of strategies has been adopted, including the fabrication of semiconductor composites, substitution of impurities for achieving extended absorbance, and coating with a metal to promote charge transfer. Despite these efforts, a photocatalyst exhibiting requisite efficiency has not been developed. This article reviews the factors governing the water splitting photoactivity of an SC material, and provides an account of our recent research on this subject. As per our investigations, the mode of adsorption of the water molecules on the semiconductor surface and their subsequent interaction with the charge carriers play a crucial role in the overall performance of a water splitting photocatalyst, rather than the much-discussed SC SC or SC -> metal charge transfer effects alone. The water to-SC binding is controlled by a combination of several physicochemical properties of a composite PC, such as the preparation-dependent grain morphology, doping affected grain nucleation, pore structure-dependent water adsorption/desorption kinetics, exposure of specific facets, and SC/SC or SC/metal interfacial characteristics. Our studies revealed strong particle size dependence and the facet-based sensitivity of modified metal sulfide and metal oxide photocatalysts. Additionally, the effect of lattice impurity on quantum efficiency of wide gap metal oxides, such as TiO2, In2TiO5, InVO4, FeNbO4, GaNbO4, GaFeO3, and LaInO3, is related to the lattice-defect-induced intra-bandgap energy levels rather than the doping-induced extension of visible region absorbance. Furthermore, the dispersed gold natoparticles served as distinct reaction sites over the surface of a TiO2 photocatalyst besides their contribution to the plasmonic effect. Our study revealed that under certain spectral overlap conditions, the inter-semiconductor charge transfer might cause quenching of the water splitting photoactivity Of a composite photocatalyst. We surmise that considering the aforementioned factors should assist in designing an efficient water splitting PC, eventually triggering technological advancements in this field.